2023
DOI: 10.1111/cpr.13495
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahedral framework nucleic acid loaded with glabridin: A transdermal delivery system applicated to anti‐hyperpigmentation

Abstract: Topical application of tyrosinase inhibitors, such as hydroquinone and arbutin, is the most common clinical treatment for hyperpigmentation. Glabridin (Gla) is a natural isoflavone that inhibits tyrosinase activity, free radical scavenging, and antioxidation. However, its water solubility is poor, and it cannot pass through the human skin barrier alone. Tetrahedral framework nucleic acid (tFNA), a new type of DNA biomaterial, can penetrate cells and tissues and can be used as carriers to deliver small‐molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
(122 reference statements)
0
3
0
Order By: Relevance
“…In addition above, TDD is a promising drug administration method because of its non/minimally invasive nature and high levels of patient compliance. Considering previous findings that tFNA can act as a carrier due to its unique spatial structure that permits skin penetration, , the ability of the BiRDS to cross the epidermal barrier as well as deeply infiltrate the dermis was assessed based on in vivo fluorescence imaging (Lumina III IVIS; PerkinElmer). After 24 h of drug penetration, the miRNA was not detectable while the BiRDS displayed a robust fluorescence signal akin to that of tFNA (Figures E and F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition above, TDD is a promising drug administration method because of its non/minimally invasive nature and high levels of patient compliance. Considering previous findings that tFNA can act as a carrier due to its unique spatial structure that permits skin penetration, , the ability of the BiRDS to cross the epidermal barrier as well as deeply infiltrate the dermis was assessed based on in vivo fluorescence imaging (Lumina III IVIS; PerkinElmer). After 24 h of drug penetration, the miRNA was not detectable while the BiRDS displayed a robust fluorescence signal akin to that of tFNA (Figures E and F).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, nucleic acid–based nanomaterials have received growing attention because of their superior editability and biological compatibility with miRNA therapeutics compared to other miRNA carriers. For instance, because of their self-assembly features, structural stability, satisfactory edibility, and biocompatibility, tetrahedral framework nucleic acids (tFNAs), which are spatial tetrahedral nanostructures created through programmed self-assembly, have drawn a lot of interest within the fields of medication delivery, sickness treatment, as well as medical imaging. Recent research has demonstrated that tFNAs can deeply get into the dermis as well as cross the skin barrier in a noninvasive way, thereby indicating the natural advantages of tFNAs for use as remarkable drug delivery vehicles. More significantly, earlier research has demonstrated that tFNAs can promote wound recovery in the skin along with lessen the formation of scars in vivo, as well as boost growth factor release and reduce inflammatory responses in vitro; these observations suggest the potential about tFNAs to exert synergistic effects upon combination with therapeutic miRNAs. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…The study aimed to assess whether the tFNA-Gla compound system could effectively reduce hyperpigmentation by inhibiting melanin production and whether it exhibited synergistic effects. Results indicated successful pigmentation treatment by inhibiting regulatory proteins related to melanin production, suggesting the potential of the tFNA-based transdermal drug delivery system as a non-invasive treatment option for epidermal and superficial dermal diseases [110]. The development of this type of nanoparticle represents a recent and innovative approach to encapsulation, with the potential for further exploration for this and other applications.…”
Section: Protein Nanoparticles For the Delivery Of Whitening Act-mentioning
confidence: 98%